Systematic Review of Pulmonary Function and Cognition in Aging. (31st October 2018) - Duggan, Emily Clare; Graham, Raquel B; Piccinin, Andrea M; Jenkins, Natalie D; Clouston, Sean; Muniz-Terrera, Graciela; Hofer, Scott M
Abstract: Background: Substantial research is dedicated to understanding the aging-related dynamics among individual differences in level, change, and variation across physical and cognitive abilities. Evaluating replicability and synthesizing findings has been limited by differences in measurements, samples, study design, and statistical analyses that confound between-person differences with within-person changes. Here, we systematically reviewed longitudinal results on the aging-related dynamics linking pulmonary function and cognitive performance. Methods: Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines were used to systematically review longitudinal studies of pulmonary function and cognition. Results: Only four studies thoroughly investigating cognitive and pulmonary longitudinal associations (three or more measurement occasions) were identified. Expanded review criteria identified three studies reporting two measurement occasions, and seven studies reporting one measurement of pulmonary function or cognition and two or more measurements of the other. We identified numerous methodological quality and risk for bias issues across studies. Conclusions: Despite documented correlational associations between pulmonary function and cognition, these results show there is very limited research thoroughly investigating their longitudinal associations. This highlights the need for longitudinal data, rigorous methodological design including key covariates, and clear communication of methods and analyses to facilitate replication across an array of samples. We recommend systematic study of outcome measures and covariates, inclusion of multiple measures (e.g., peak expiratory flow, forced expiratory volume in 1 s, and forced vital capacity), as well as application of the same analytic approach across multiple datasets.